“Um crime inominável”: mulheres infanticidas, trabalho e etnia no sul do Brasil (1909-1928) - Pötter, Deise de Siqueira (2019)
This study is part of the work on the Frontier, Politics and Society research line, which is linked to the Postgraduate Program in History of the Federal University of Santa Maria (PPGH-UFSM). The proposed research has as its theme the women who were accused of the crime of infanticide in the south of the country in the first decades of the twentieth century, in this sense, the research focuses more precisely Alegrete, Sant'Ana do Livramento and Dom Pedrito. The spatial choice was due to the inexistence of studies on the subject in the region. With respect to the temporal cut, this had as its initial beacon the Criminal Code of the United States of Brazil, which came into force in 1890 and lasted until 1940. Based on this period, fifteen criminal cases (1909- 1939) were found in the State Public Archive of Rio Grande do Sul - APERS. The treatment of these sources is based on analyzes of the qualitative aspects, considering possible contradictions that the document may present, among other specific dangers of documentation. That said, the discussion focuses on the analysis of infanticide crimes and their relationship to honor, as well as gender, ethnicity, and work. For this, it is necessary to: a) Evidence of what the society of the analyzed period comprised by family, honor and their relation and implications with the gender; b) Know the history of some women who did not follow the moral standards stipulated for the period and ended with an unwanted pregnancy and the solutions they found to end their problem; c) Know the role of the complainant through the initiation of police investigations, as well as their profile; d) To understand how the knowledge of Legal Medicine was being incorporated in the juridical field and its importance in the search for the truth through the bodies; e) To verify the outcomes given to the crimes of infanticide, observing the speeches alleged in defense of the grounds.